A cerium dioxide-coated polyimide composite nanofiber membrane and preparation method thereof
Cover the composite nanofiber membrane of polytamine -pickedly picilline -dioxide puppets through electrostatic spinning, and solve the lack of traditional lithium -ion battery diaphragm in terms of high magnification and discharge and high temperature resistance. Firelly lithium ion battery diaphragm material.
Patent Information
- Application Number
- CN202111301229.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-04
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-11-04
AI Technical Summary
Traditional lithium-ion battery separators have shortcomings in their high-rate charging and discharging performance and high-temperature resistance, which are difficult to meet social needs, especially in terms of battery safety.
The static spinning method is used to prepare a composite nano -fiber membrane of the polybinamide pyrumine. By covering the nano -nanofibilized film of the polyimide nanopotic membrane, it improves its high temperature, flame retardant, infiltration and intensity Essence
The high pore rate, excellent high temperature resistance, thermal size stability, flame retardability and high strength are suitable for new lithium ion battery diaphragm materials.
Smart Images

Figure CN113897775B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyimide nanofiber membranes, and relates to a cerium dioxide-coated polyimide composite nanofiber membrane and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have become one of the most promising green and environmentally friendly energy sources with their high energy density and low environmental pollution. However, traditional lithium-ion batteries have gradually failed to meet the rapidly growing social needs in terms of high-rate charge and discharge performance and high-temperature resistance. In the battery structure, the battery separator plays a role in preventing the positive and negative electrodes from contacting each other and providing ion transmission channels. The performance of the battery separator is an important determinant of battery performance. Polyolefin separators first occupied the lithium-ion battery separator market with their advantages of high mechanical strength and good chemical stability. However, with the continuous improvement of people's requirements for battery energy density, endurance, and especially battery safety, polyolefin separators have exposed some significant shortcomings, and their low thermal transition temperature seriously affects battery safety, greatly restricting the development of lithium-ion batteries. Traditional battery separators use polyolefins as raw materials, with poor electrolyte wettability and poor thermal stability, making it difficult to ensure the high-rate charge and discharge performance and high-temperature resistance of the battery. Therefore, the development of new lithium-ion battery separators with high thermal stability and high electrolyte wettability is an urgent need in the field of lithium-ion battery research.
[0003] The principle of electrospinning technology is: as the syringe is pushed, the polymer solution stored in the syringe is squeezed out of the needle; due to the influence of the high-voltage electrostatic field, the polymer solution squeezed out of the needle will deform to form a conical droplet called a "Taylor cone"; as the voltage increases, the droplet deformation continues to increase, and when the voltage reaches a certain value, the solution will overcome the surface tension and form a jet; the movement of the jet will gradually become disordered under the action of electrostatic repulsion; during the movement, the solvent continues to evaporate, and eventually the jet will solidify to form fibers and accumulate disorderly on the surface of the receiver. At present, the electrospinning process can already prepare nanofiber materials with various morphologies such as coaxial fibers, hollow fibers, and porous fibers, which have broad application prospects in filtration, medical treatment, catalysis, energy and other industries.
[0004] Polyimide is a high-performance polymer with a special imide ring on the main chain. Thanks to its rigid main chain and the strong conjugation effect between the imide ring and the aromatic ring structure, polyimide materials have high main chain bond energy and strong intermolecular hydrogen bonding force. This gives polyimide a series of remarkable excellent properties. Polyimide materials have excellent mechanical strength; low dielectric constant, excellent dielectric properties, insulation properties; excellent thermal stability and flame retardant properties; excellent chemical stability. The polyimide nanofiber membrane made by electrospinning, in addition to the properties of polyimide mentioned above, also has high porosity, flexibility and other properties, making polyimide nanofiber membrane one of the best choices for the new generation of high temperature resistant and high safety lithium-ion battery separators. Coating a layer of inorganic ceramic on the surface of polyimide nanofiber can further improve the temperature resistance, flame retardancy, wettability and strength of the polyimide nanofiber membrane, while improving the shortcomings of inorganic ceramics in terms of lack of flexibility, and realizing the preparation of "inorganic ceramic" coated polyimide fiber flexible diaphragm. Cerium oxide, as a new type of ceramic material, has outstanding high temperature resistance, wettability and flame retardancy. The present invention adopts organic polymer material polyimide fiber as a matrix and combines it with inorganic material cerium dioxide to prepare a cerium dioxide coated polyimide composite nanofiber membrane, establishes a new method, and realizes the controllable coating of cerium dioxide inorganic ceramic layer on polyimide nanofiber. The composite nanofiber membrane has outstanding high temperature resistance, flame retardancy, wettability, flexibility, excellent strength and porosity, and can be used as a new type of lithium ion battery diaphragm material. Summary of the invention
[0005] The present invention provides a cerium dioxide-coated polyimide composite nanofiber membrane and a preparation method thereof, which has excellent heat resistance, high porosity, chemical stability, thermal dimensional stability, mechanical properties and wettability.
[0006] The polyimide composite nanofiber membrane is coated with cerium dioxide, and the surface of the polyimide fiber membrane has a cerium dioxide layer. The thickness of the polyimide fiber membrane is 10-40 μm, the diameter of the fiber in the polyimide fiber membrane is 10-800 nm, and the thickness of the cerium dioxide layer is 2-200 nm.
[0007] Furthermore, the porosity of the cerium dioxide-coated polyimide composite nanofiber membrane is 80%-95%, preferably 85%-92%.
[0008] Furthermore, the thickness of the polyimide fiber membrane is preferably 15-20 μm.
[0009] Furthermore, the diameter of the fiber in the polyimide fiber membrane is preferably 20-700 nm, and the thickness of the cerium dioxide layer is preferably 5-100 nm.
[0010] A method for preparing a cerium dioxide-coated polyimide composite nanofiber membrane comprises the following steps:
[0011] A: dissolving cerium salt in water to obtain a precursor solution of cerium dioxide with a concentration of 0.01-3 mol / L;
[0012] B: preparing a polyamic acid nanofiber membrane by electrospinning a polyamic acid solution having a concentration of 3wt%-25wt%;
[0013] C: placing the polyamic acid nanofiber membrane in the cerium dioxide precursor solution, adding hydrogen peroxide to react, and adjusting the pH value of the solution to 8-14 after the reaction.
[0014] D: The nanofiber membrane obtained in step C is subjected to heat treatment to obtain a polyimide nanofiber membrane with a surface coated with a cerium dioxide nanolayer.
[0015] Furthermore, the cerium salt described in step A is cerium nitrate, cerium chloride, ammonium cerium nitrate and cerium carbonate, and the concentration of cerium ions in the cerium dioxide precursor solution is preferably 0.05-2.5 mol / L, particularly preferably 0.1-2 mol / L.
[0016] Furthermore, in step B, a polyamic acid solution is synthesized by condensation polymerization of dibasic anhydride and diamine monomers, wherein the dibasic anhydride is pyromellitic anhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic anhydride (BPDA), 3,3',4,4'-benzophenonetetracarboxylic anhydride (BTDA), 3,3',4,4'-diphenyl ether tetracarboxylic anhydride (ODPA), hexafluorodianhydride (6FDA), bisphenol A type dianhydride (BPADA), etc., and the diamine is 4,4'-diaminodiphenyl ether (4,4'-ODA), p-phenylenediamine (p-PDA), 2-(4-aminophenyl)-5-aminobenzimidazole (BIA), biphenylenediamine (BPA), etc.
[0017] The concentration of the polyamic acid solution is preferably 4 to 25 wt %, particularly preferably 5 to 20 wt %.
[0018] The non-protonic polar solvent used for synthesizing the polyamic acid solution is one or more of N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide and the like.
[0019] Electrospinning is a special fiber manufacturing process, in which a polymer solution or melt is jet-spun in a strong electric field. Under the action of the electric field, the droplet at the needle tip changes from a sphere to a cone (i.e., a "Taylor cone"), and fiber filaments are extended from the tip of the cone. This method can produce polymer filaments with nanometer diameters. The present invention uses a polyamic acid solution as an electrospinning solution and prepares it into nanofibers by electrospinning. In this process, in addition to the influence of the spinning concentration, the necessary spinning parameters are also one of the reasons for the success of electrospinning. Taking needle spinning as an example, the voltage is 20-30KV, the propulsion amount is 0.3-0.7mL / h, and a No. 18 needle is selected, and the speed of the receiving roller is 300-600rpm.
[0020] Furthermore, in step C, the treatment time of the polyamic acid nanofiber membrane in the precursor solution of cerium dioxide is 1 min-3 h, preferably 2 min-2 h, and particularly preferably 10 min-1 h; the pH value of the precursor solution of cerium dioxide (whether this pH value is that of the precursor solution) is 1-6.5, preferably 2-6; the concentration of the added hydrogen peroxide is 1%-20%, preferably 2%-15%, and particularly preferably 3%-10%; the reaction time is 0.5-30 min, preferably 1-25 min; the pH value of the solution after the reaction is adjusted to 8-14, preferably 9-13, and further, the pH value of the solution after the reaction is adjusted by adding dilute ammonia water.
[0021] Furthermore, the heat treatment time in step D is 0.1-5h, preferably 1-4h. The heat treatment conditions are heating from room temperature to 250-400°C, preferably 300-350°C, and the heating rate is 1-20°C / min, preferably 2-10°C / min.
[0022] Compared with the prior art, the present invention has the following excellent effects:
[0023] 1. The present invention establishes a new method to achieve the preparation of a composite nanofiber membrane with polyimide nanofiber as the matrix and coated with a cerium dioxide inorganic ceramic layer, and the cerium dioxide-coated polyimide composite nanofiber membrane has the potential to be used as a new high-performance lithium battery separator and is a new type of organic-inorganic composite material.
[0024] 2. The cerium dioxide-coated polyimide composite nanofiber membrane prepared by the present invention has excellent high temperature resistance (can withstand 500°C high temperature), thermal dimensional stability (shrinkage rate is 0 at 300°C), wettability (contact angle with electrolyte is about 12°C), and thermal conductivity (can withstand 500°C high temperature).
[0025] ), flame retardancy, high porosity (up to 92%), high strength (up to 50.8MPa), etc.
[0026] 3. By utilizing the adsorption and complexing properties of the nanofiber membrane to allow the inorganic material precursor to adsorb and nucleate on the nanofiber surface, a polyimide nanofiber membrane coaxially coated with inorganic ceramics can be prepared. Compared with the multilayer membrane prepared by the coating method, this nanofiber membrane will have a more uniform fiber structure, lighter weight and better electrolyte wettability.
[0027] 4. The cerium dioxide-coated polyimide composite nanofiber membrane prepared by the present invention can realize the controllable preparation of nanofiber membranes with different nanofiber diameters and different thicknesses and the controllable coating of cerium dioxide on the fiber membrane surface by adjusting the process parameters. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a scanning electron microscope image of the cerium dioxide-coated polyimide composite nanofiber membrane prepared according to Example 1, with the magnification of the left image being 30,000 times and the right image being 2,000 times;
[0029] Figure 2 This is a scanning electron microscope image of the cerium dioxide-coated polyimide composite nanofiber membrane prepared according to Example 2, with the magnification of the left image being 30,000 times and the right image being 2,000 times;
[0030] Figure 3 This is a scanning electron microscope image of the cerium dioxide-coated polyimide composite nanofiber membrane prepared according to Example 3, with the magnification of the left image being 30,000 times and the right image being 2,000 times;
[0031] Figure 4 This is a scanning electron microscope image of the cerium dioxide-coated polyimide composite nanofiber membrane prepared according to Example 4, with the magnification of the left image being 30,000 times and the right image being 2,000 times.
[0032] Figure 5 This is a scanning electron microscope image of the cerium dioxide-coated polyimide composite nanofiber membrane prepared according to Example 5, with the magnification of the left image being 30,000 times and the right image being 2,000 times.
[0033] Figure 6 This is a scanning electron microscope image of the polyimide nanofiber membrane prepared in Example 1, with the magnification of the left image being 50,000 times and the right image being 2,000 times.
[0034] Figure 7 This is a scanning electron microscope image of the ash obtained by calcining the cerium dioxide-coated polyimide composite nanofiber membrane prepared in Example 1 at 900°C for 1.5 hours. The magnification of the left image is 30,000 times, and the right image is 2,000 times. DETAILED DESCRIPTION
[0035] The invention is further described below in conjunction with specific examples. It should be noted that the following examples are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Therefore, although the present invention has been described in detail in this specification with reference to the following examples, it should be understood by those skilled in the art that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.
[0036] Example 1
[0037] The PMDA / ODA system polyamic acid nanofiber membrane was prepared by first placing it in a 0.1 mol / L cerium dioxide precursor solution for 60 min, adding 5 ml of hydrogen peroxide, and then heat-treating it to obtain a cerium dioxide-coated polyimide composite nanofiber membrane. (1) Weigh 2.0 g of pyromellitic anhydride (PMDA) and 1.8 g of 4,4'-diaminodiphenyl ether (ODA) in a molar ratio of 1:1, dissolve all of the ODA in 30 ml of N,N-dimethylformamide (DMF) solvent, stir mechanically, and after all of the ODA is dissolved in DMF, add PMDA step by step under ice-water bath conditions to obtain a polyamic acid solution with moderate viscosity. After mechanical stirring for 2 hours, the polyamic acid solution is loaded into a 20 ml syringe and the polyamic acid fiber membrane is prepared by electrospinning technology. The specific parameters of the electrospinning machine are spinning voltage: 29 kV; spinning temperature: room temperature; spinning humidity: 30%; syringe needle diameter: No. 18; receiving roller speed: 500 m / min; receiving distance: 20 cm. The prepared polyamic acid fiber membrane is placed in a clean bench for 12 hours. (2) Measure 30 ml of deionized water and mix it evenly in a beaker. Weigh 1.627 g of cerium nitrate hexahydrate, add it to deionized water, and stir to fully dissolve it to obtain a precursor solution of cerium dioxide. (3) Place the polyamic acid nanofiber membrane in the 0.1 mol / L precursor solution of cerium dioxide for 60 min, the same below. (4) Add 5 ml of H 2 O 2 , fully react for 20 minutes, then drip 10 drops of dilute ammonia water (pH value is 9-13, the pH value here should be a point value, the same below), take out and dry. (5) The nanofiber membrane obtained in the previous step is placed in a hot furnace, and the temperature is gradually increased to 350℃ at a heating rate of 4℃ / min, and maintained for 1h to obtain a polyimide nanofiber membrane with a surface coated with cerium dioxide. The obtained fiber morphology is shown in the attached figure. Figure 1 The shrinkage rate of the polyimide composite nanofiber membrane coated with cerium dioxide prepared in Example 1 after being kept at 400° C. for 1 hour was 0, and the tensile strength was 35.4 MPa.
[0038] Comparative Example 1
[0039] Preparation of PMDA / ODA system polyamic acid nanofiber membrane, and obtaining polyimide nanofiber membrane after thermal imidization. (1) Weigh 2.0 g of pyromellitic anhydride (PMDA) and 1.8 g of 4,4'-diaminodiphenyl ether (ODA) in a molar ratio of 1:1, dissolve all of ODA in 30 ml of N,N-dimethylformamide (DMF) solvent, stir mechanically, and after ODA is completely dissolved in DMF, add PMDA step by step under ice water bath to obtain a polyamic acid solution with moderate viscosity, stir mechanically for 2 hours, and then load the polyamic acid solution into a 20 ml syringe, and prepare polyamic acid fiber membrane by electrospinning technology. The specific parameters of the electrospinning machine are spinning voltage: 29 kV; spinning temperature: room temperature; spinning humidity: 30%; syringe needle diameter: No. 18; receiving roller speed: 500 m / min; receiving distance: 20 cm. The prepared polyamic acid fiber membrane was placed in a clean bench for 12 hours; the obtained polyamic acid fiber membrane was placed in a hot furnace, gradually heated to 350°C at a heating rate of 4°C / min, and maintained for 1 hour, thereby preparing a polyimide nanofiber membrane. The polyimide nanofiber membrane prepared in Comparative Example 1 had a shrinkage rate of 0.3% and a tensile strength of 13.3 MPa at 400°C for 1 hour.
[0040] Example 2
[0041] The PMDA / ODA system polyamic acid nanofiber membrane was prepared by first placing it in a 0.1 mol / L cerium dioxide precursor solution for 30 min, adding 5 ml of hydrogen peroxide, and then heat-treating it to obtain a cerium dioxide-coated polyimide composite nanofiber membrane. (1) Weigh 2.0 g of pyromellitic anhydride (PMDA) and 1.8 g of 4,4'-diaminodiphenyl ether (ODA) in a molar ratio of 1:1, dissolve all of the ODA in 30 ml of N,N-dimethylformamide (DMF) solvent, stir mechanically, and after all of the ODA is dissolved in DMF, add PMDA step by step under ice-water bath conditions to obtain a polyamic acid solution with moderate viscosity. After mechanical stirring for 2 hours, the polyamic acid solution is loaded into a 20 ml syringe and the polyamic acid fiber membrane is prepared by electrospinning technology. The specific parameters of the electrospinning machine are spinning voltage: 29 kV; spinning temperature: room temperature; spinning humidity: 30%; syringe needle diameter: No. 18; receiving roller speed: 500 m / min; receiving distance: 20 cm. The prepared polyamic acid fiber membrane is placed in a clean bench for 12 hours. (2) Measure 30 ml of deionized water and mix it evenly in a beaker. Weigh 1.627 g of cerium nitrate hexahydrate, add it to deionized water, and stir to fully dissolve it to obtain a precursor solution of cerium dioxide. (3) Place the polyamic acid nanofiber membrane in the 0.1 mol / L precursor solution of cerium dioxide for 30 min. (4) Add 5 ml of H 2 O 2, fully react for 20 minutes, then add 10 drops of dilute ammonia water (pH 9-13), take out and dry. (5) Place the nanofiber membrane obtained in the previous step in a hot furnace, gradually heat it to 350°C at a heating rate of 4°C / min, and keep it for 1 hour to obtain a polyimide nanofiber membrane coated with cerium dioxide on the surface. The obtained fiber morphology is as shown in the attached figure. Figure 2 The shrinkage rate of the polyimide composite nanofiber membrane coated with cerium dioxide prepared in Example 2 was 0 after being kept at 400°C for 1 hour, and the tensile strength was 33.6 MPa.
[0042] Comparative Example 2
[0043] Preparation of PMDA / ODA system polyamic acid nanofiber membrane, and obtaining polyimide nanofiber membrane after thermal imidization. (1) Weigh 2.0 g of pyromellitic anhydride (PMDA) and 1.8 g of 4,4'-diaminodiphenyl ether (ODA) in a molar ratio of 1:1, dissolve all of ODA in 30 ml of N,N-dimethylformamide (DMF) solvent, stir mechanically, and after ODA is completely dissolved in DMF, add PMDA step by step under ice water bath to obtain a polyamic acid solution with moderate viscosity, stir mechanically for 2 hours, and then load the polyamic acid solution into a 20 ml syringe, and prepare polyamic acid fiber membrane by electrospinning technology. The specific parameters of the electrospinning machine are spinning voltage: 29 kV; spinning temperature: room temperature; spinning humidity: 30%; syringe needle diameter: No. 18; receiving roller speed: 500 m / min; receiving distance: 20 cm. The prepared polyamic acid fiber membrane was placed in a clean bench for 12 hours; the obtained polyamic acid fiber membrane was placed in a hot furnace, gradually heated to 350°C at a heating rate of 4°C / min, and maintained for 1 hour, thereby preparing a polyimide nanofiber membrane. The polyimide nanofiber membrane prepared in Comparative Example 2 had a shrinkage rate of 0.3% and a tensile strength of 13.3 MPa at 400°C for 1 hour.
[0044] Example 3
[0045] The PMDA / ODA system polyamic acid nanofiber membrane was prepared by first placing it in a 0.1 mol / L cerium dioxide precursor solution for 10 min, adding 5 ml of hydrogen peroxide, and then heat-treating it to obtain a cerium dioxide-coated polyimide composite nanofiber membrane. (1) Weigh 2.0 g of pyromellitic anhydride (PMDA) and 1.8 g of 4,4'-diaminodiphenyl ether (ODA) in a molar ratio of 1:1, dissolve all of the ODA in 30 ml of N,N-dimethylformamide (DMF) solvent, stir mechanically, and after all of the ODA is dissolved in DMF, add PMDA step by step under ice-water bath conditions to obtain a polyamic acid solution with moderate viscosity. After mechanical stirring for 2 hours, the polyamic acid solution is loaded into a 20 ml syringe and the polyamic acid fiber membrane is prepared by electrospinning technology. The specific parameters of the electrospinning machine are spinning voltage: 29 kV; spinning temperature: room temperature; spinning humidity: 30%; syringe needle diameter: No. 18; receiving roller speed: 500 m / min; receiving distance: 20 cm. The prepared polyamic acid fiber membrane is placed in a clean bench for 12 hours. (2) Measure 30 ml of deionized water and mix it evenly in a beaker. Weigh 1.627 g of cerium nitrate hexahydrate, add it to deionized water, and stir to fully dissolve it to obtain a precursor solution of cerium dioxide. (3) Place the polyamic acid nanofiber membrane in the 0.1 mol / L precursor solution of cerium dioxide for 10 min. (4) Add 5 ml of H 2 O 2 , fully react for 20 minutes, then add 10 drops of dilute ammonia water (pH 9-13), take out and dry. (5) Place the nanofiber membrane obtained in the previous step in a hot furnace, gradually heat it to 350°C at a heating rate of 4°C / min, and keep it for 1 hour to obtain a polyimide nanofiber membrane coated with cerium dioxide on the surface. The obtained fiber morphology is as shown in the attached figure. Figure 3 The shrinkage rate of the polyimide composite nanofiber membrane coated with cerium dioxide prepared in Example 3 after being kept at 400°C for 1 hour was 0, and the tensile strength was 30.9 MPa.
[0046] Comparative Example 3
[0047] Preparation of PMDA / ODA system polyamic acid nanofiber membrane, and obtaining polyimide nanofiber membrane after thermal imidization. (1) Weigh 2.0 g of pyromellitic anhydride (PMDA) and 1.8 g of 4,4'-diaminodiphenyl ether (ODA) in a molar ratio of 1:1, dissolve all of ODA in 30 ml of N,N-dimethylformamide (DMF) solvent, stir mechanically, and after ODA is completely dissolved in DMF, add PMDA step by step under ice water bath to obtain a polyamic acid solution with moderate viscosity, stir mechanically for 2 hours, and then load the polyamic acid solution into a 20 ml syringe, and prepare polyamic acid fiber membrane by electrospinning technology. The specific parameters of the electrospinning machine are spinning voltage: 29 kV; spinning temperature: room temperature; spinning humidity: 30%; syringe needle diameter: No. 18; receiving roller speed: 500 m / min; receiving distance: 20 cm. The prepared polyamic acid fiber membrane was placed in a clean bench for 12 hours; the obtained polyamic acid fiber membrane was placed in a hot furnace, gradually heated to 350°C at a heating rate of 4°C / min, and maintained for 1 hour, thereby preparing a polyimide nanofiber membrane. The shrinkage rate of the polyimide nanofiber membrane prepared in Comparative Example 3 was 0.3% when kept at 400°C for 1 hour, and the tensile strength was 13.3MPa.
[0048] Example 4
[0049] The PMDA / ODA system polyamic acid nanofiber membrane was prepared by first placing it in a 1 mol / L cerium dioxide precursor solution for 60 min, adding 5 ml of hydrogen peroxide, and then heat-treating it to obtain a cerium dioxide-coated polyimide composite nanofiber membrane. (1) Weigh 2.0 g of pyromellitic anhydride (PMDA) and 1.8 g of 4,4'-diaminodiphenyl ether (ODA) in a molar ratio of 1:1, dissolve all of the ODA in 30 ml of N,N-dimethylformamide (DMF) solvent, stir mechanically, and after all of the ODA is dissolved in DMF, add PMDA step by step under ice-water bath conditions to obtain a polyamic acid solution with moderate viscosity. After mechanical stirring for 2 hours, the polyamic acid solution is loaded into a 20 ml syringe and the polyamic acid fiber membrane is prepared by electrospinning technology. The specific parameters of the electrospinning machine are spinning voltage: 29 kV; spinning temperature: room temperature; spinning humidity: 30%; syringe needle diameter: No. 18; receiving roller speed: 500 m / min; receiving distance: 20 cm. The prepared polyamic acid fiber membrane is placed in a clean bench for 12 hours. (2) Measure 30 ml of deionized water and mix it evenly in a beaker. Weigh 1.627g of cerium nitrate hexahydrate, add it to deionized water, and stir to fully dissolve it to obtain a precursor solution of cerium dioxide. (3) Place the polyamic acid nanofiber membrane in a 1mol / L cerium dioxide precursor solution for 60min. (4) Add 5ml of H2 O 2 , fully react for 20 minutes, then add 10 drops of dilute ammonia water (pH 9-13), take out and dry. (5) Place the nanofiber membrane obtained in the previous step in a hot furnace, gradually heat it to 350°C at a heating rate of 4°C / min, and keep it for 1 hour to obtain a polyimide nanofiber membrane coated with cerium dioxide on the surface. The obtained fiber morphology is as shown in the attached figure. Figure 4 The shrinkage rate of the polyimide composite nanofiber membrane coated with cerium dioxide prepared in Example 4 was 0 after being kept at 400°C for 1 hour, and the tensile strength was 34.5 MPa.
[0050] Comparative Example 4
[0051] Preparation of PMDA / ODA system polyamic acid nanofiber membrane, and obtaining polyimide nanofiber membrane after thermal imidization. (1) Weigh 2.0 g of pyromellitic anhydride (PMDA) and 1.8 g of 4,4'-diaminodiphenyl ether (ODA) in a molar ratio of 1:1, dissolve all of ODA in 30 ml of N,N-dimethylformamide (DMF) solvent, stir mechanically, and after ODA is completely dissolved in DMF, add PMDA step by step under ice water bath to obtain a polyamic acid solution with moderate viscosity, stir mechanically for 2 hours, and then load the polyamic acid solution into a 20 ml syringe, and prepare polyamic acid fiber membrane by electrospinning technology. The specific parameters of the electrospinning machine are spinning voltage: 29 kV; spinning temperature: room temperature; spinning humidity: 30%; syringe needle diameter: No. 18; receiving roller speed: 500 m / min; receiving distance: 20 cm. The prepared polyamic acid fiber membrane was placed in a clean bench for 12 hours; the obtained polyamic acid fiber membrane was placed in a hot furnace, gradually heated to 350°C at a heating rate of 4°C / min, and maintained for 1 hour, thereby preparing a polyimide nanofiber membrane. The shrinkage rate of the polyimide nanofiber membrane prepared in Comparative Example 4 was 0.3% when kept at 400°C for 1 hour, and the tensile strength was 13.3 MPa.
[0052] Example 5
[0053] The PMDA / ODA system polyamic acid nanofiber membrane was prepared by first placing it in a 1 mol / L cerium dioxide precursor solution for 30 min, adding 5 ml of hydrogen peroxide, and then heat-treating it to obtain a cerium dioxide-coated polyimide composite nanofiber membrane. (1) Weigh 2.0 g of pyromellitic anhydride (PMDA) and 1.8 g of 4,4'-diaminodiphenyl ether (ODA) in a molar ratio of 1:1, dissolve all of the ODA in 30 ml of N,N-dimethylformamide (DMF) solvent, stir mechanically, and after all of the ODA is dissolved in DMF, add PMDA step by step under ice-water bath conditions to obtain a polyamic acid solution with moderate viscosity. After mechanical stirring for 2 hours, the polyamic acid solution is loaded into a 20 ml syringe and the polyamic acid fiber membrane is prepared by electrospinning technology. The specific parameters of the electrospinning machine are spinning voltage: 29 kV; spinning temperature: room temperature; spinning humidity: 30%; syringe needle diameter: No. 18; receiving roller speed: 500 m / min; receiving distance: 20 cm. The prepared polyamic acid fiber membrane is placed in a clean bench for 12 hours. (2) Measure 30 ml of deionized water and mix it evenly in a beaker. Weigh 1.627 g of cerium nitrate hexahydrate, add it to deionized water, and stir to fully dissolve it to obtain a precursor solution of cerium dioxide. (3) Place the polyamic acid nanofiber membrane in the 1 mol / L precursor solution of cerium dioxide for 60 min. (4) Add 5 ml of H 2 O 2 , fully react for 20 minutes, then add 10 drops of dilute ammonia water (pH 9-13), take out and dry. (5) Place the nanofiber membrane obtained in the previous step in a hot furnace, gradually heat it to 350°C at a heating rate of 4°C / min, and keep it for 1 hour to obtain a polyimide nanofiber membrane coated with cerium dioxide on the surface. The obtained fiber morphology is as shown in the attached figure. Figure 5 The shrinkage rate of the polyimide composite nanofiber membrane coated with cerium dioxide prepared in Example 5 was 0 after being kept at 400°C for 1 hour, and the tensile strength was 32.9 MPa.
[0054] Comparative Example 5
[0055] Preparation of PMDA / ODA system polyamic acid nanofiber membrane, and obtaining polyimide nanofiber membrane after thermal imidization. (1) Weigh 2.0 g of pyromellitic anhydride (PMDA) and 1.8 g of 4,4'-diaminodiphenyl ether (ODA) in a molar ratio of 1:1, dissolve all of ODA in 30 ml of N,N-dimethylformamide (DMF) solvent, stir mechanically, and after ODA is completely dissolved in DMF, add PMDA step by step under ice water bath to obtain a polyamic acid solution with moderate viscosity, stir mechanically for 2 hours, and then load the polyamic acid solution into a 20 ml syringe, and prepare polyamic acid fiber membrane by electrospinning technology. The specific parameters of the electrospinning machine are spinning voltage: 29 kV; spinning temperature: room temperature; spinning humidity: 30%; syringe needle diameter: No. 18; receiving roller speed: 500 m / min; receiving distance: 20 cm. The prepared polyamic acid fiber membrane was placed in a clean bench for 12 hours; the obtained polyamic acid fiber membrane was placed in a hot furnace, gradually heated to 350°C at a heating rate of 4°C / min, and maintained for 1 hour, thereby preparing a polyimide nanofiber membrane. The polyimide nanofiber membrane prepared in Comparative Example 5 had a shrinkage rate of 0.3% and a tensile strength of 13.3 MPa at 400°C for 1 hour.
[0056] Experimental tests show that through Figure 6 Pure polyimide nanofiber membrane and Figure 1-5 By comparing the scanning electron microscope images of the cerium dioxide coated polyimide composite nanofiber membrane, it can be clearly seen that the fiber surface of the pure polyimide nanofiber membrane is smooth, while a rough surface coating structure can be observed on the surface of the composite nanofiber, that is, the cerium dioxide nanolayer is tightly coated on the surface of the polyimide fiber. Figure 7 This is a scanning electron microscope image of the ash obtained by calcining the polyimide composite nanofiber membrane coated with cerium dioxide prepared in Example 1 at 900°C for 1.5 hours. It can be observed from the image that after calcination at 900°C, there is still material remaining and it presents a fiber morphology, proving the existence of cerium dioxide. Figure 1-7 The phenomenon shows that we have successfully prepared the cerium dioxide-coated polyimide composite nanofiber membrane.
Claims
1. A method for preparing a cerium dioxide-coated polyimide composite nanofiber membrane, characterized in that: The composite nanofiber membrane is composed of a cerium dioxide nanolayer with a coating thickness of 5-100nm and a polyimide nanofiber with a diameter of 20-650nm; The preparation method comprises the following steps: A: dissolving cerium salt in water to obtain a precursor solution of cerium dioxide with a concentration of 0.1-3 mol / L; B: preparing a polyamic acid nanofiber membrane by electrospinning a polyamic acid solution having a concentration of 3wt%-25wt%; C: placing the polyamic acid nanofiber membrane in the cerium dioxide precursor solution, adding hydrogen peroxide to react, and adjusting the pH value of the solution to 8-14 after the reaction; D: The nanofiber membrane obtained in step C is subjected to heat treatment to obtain a polyimide nanofiber membrane with a surface coated with a cerium dioxide nanolayer.
2. The preparation method according to claim 1, wherein: The cerium salt described in step A is cerium nitrate, cerium chloride, ammonium cerium nitrate and cerium carbonate.
3. The preparation method according to claim 1, wherein The concentration of the cerium dioxide precursor solution is 0.1-2.5 mol / L.
4. The preparation method according to claim 1, wherein The concentration of the cerium dioxide precursor solution is 0.1-2 mol / L.
5. The preparation method according to claim 1, wherein: In step B, a polyamic acid solution is synthesized by condensation polymerization of dibasic anhydride and diamine monomers, wherein the dibasic anhydride is pyromellitic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride, 3,3',4,4'-benzophenonetetracarboxylic anhydride, 3,3',4,4'-diphenyl ether tetracarboxylic anhydride, hexafluoroanhydride or bisphenol A type anhydride, and the diamine is 4,4'-diaminodiphenyl ether, p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole or diphenylenediamine.
6. The preparation method according to claim 1, wherein: In step C, the polyamic acid nanofiber membrane is treated in the cerium dioxide precursor solution for 1 min-3 h; the concentration of added hydrogen peroxide is 1%-20%; the reaction time is 0.5-30 min; and the pH value of the solution is adjusted to 9-13 after the reaction.
7. The preparation method according to claim 6, wherein: The pH value of the solution after the reaction was adjusted by adding dilute ammonia water.
8. The preparation method according to claim 1, wherein: The heat treatment time of step D is 0.1-5h; the heat treatment conditions are heating from room temperature to 250-400°C, and the heating rate is 1-20°C / min.
Citation Information
Patent Citations
Polyimide-zirconium dioxide composite nanofiber membrane and preparation method thereof
CN105970485A
Nonwoven fabric ceramic separator, and preparation method and application thereof
CN106784539A
Polyimide / cerium dioxide composite nanofiber membrane and preparation method thereof
CN113622089A